PENGARUH WORK EXPERIENCE, WORK ENVIRONMENT, DAN JOB SATISFACTION TERHADAP PERFORMANCE PEGAWAI NEGERI SIPIL DINAS PERTANIAN DAN KETAHANAN PANGAN DAERAH ISTIMEWA YOGYAKARTA - Margareta Yosefa; Raden Teja Yokanan (Jurnal Riset Manajemen dan Bisnis, 2023)
ABSTRACT This study entitled "The Effect Of Work Experience, Work Environment, And Job Satisfaction On The Performance Of Civil Servants Agricultural And Food Security Department Of Yogyakarta Special Region" The purpose of this study was to determine the profile of employee respondents, to find out whether Work Experience, Work Environment, and Job Satisfaction has a partial and simultaneous effect on the Performance of Civil Servants at the Department of Agriculture and Food Security in the Special Region of Yogyakarta. This type of research uses descriptive quantitative data collection techniques using questionnaires and sampling using Simple Random Sampling. This research uses validity test and reliability test. The analytical tool uses percentage analysis, classical assumption test, simple linear regression analysis, t test (partial), multiple linear regression analysis, F test (simultaneous), and the coefficient of determination . Based on the results of calculating the percentage analysis of 111 employee respondents who work at the Department of Agriculture and Food Security of the Special Region of Yogyakarta, the profiles of respondents are dominated by: female gender (55.9%), age level ≥ 35 years to <50 years (49.5%), bachelor degree (56.8%), married (79.3%), and years of service 11 to 20 years (32.4%). Furthermore, based on simple linear regression analysis the t test shows that Work Experience, Work Environment, and Job Satisfaction partially have a positive and significant effect on Employee Performance at the Department of Agriculture and Food Security in the Special Region of Yogyakarta. Based on the results of multiple linear regression analysis of the F test, it shows that Work Experience, Work Environment, and Job Satisfaction simultaneously have a positive and significant effect on Employee Performance at the Department of Agriculture and Food Security in the Special Region of Yogyakarta. Keywords: Work Experience, Work Environment, Job Satisfaction, Performance ABSTRAK Penelitian ini berjudul “PENGARUH WORK EXPERIENCE, WORK ENVIRONMENT, DAN JOB SATISFACTION TERHADAP PERFORMANCE PEGAWAI NEGERI SIPIL DINAS PERTANIAN DAN KETAHANAN PANGAN DAERAH ISTIMEWA YOGYAKARTA” tujuan dari penelitian ini adalah untuk mengetahui profil responden pegawai, untuk mengetahui apakah Work Experience, Work Environment, dan Job Satisfaction berpengaruh secara parsial dan simultan terhadap Performance Pegawai Negeri Sipil Dinas Pertanian dan Ketahanan Pangan Daerah Istimewa Yogyakarta. Jenis penelitian ini menggunakan deskriptif kuantitatif dengan teknik pengumpulan data menggunakan kuesioner dan pengambilan sampel menggunakan Simple Random Sampling. Penelitian ini menggunakan uji validitas dan uji reliabilitas. Alat analisis dengan menggunakan analisis persentase, uji asumsi klasik, analisis regresi linier sederhana, uji t (parsial), analisis regresi linier berganda, uji F (simultan), dan koefisien determinasi . Berdasarkan hasil perhitungan analisis persentase dari 111 responden pegawai yang bekerja di Dinas Pertanian dan Ketahanan Pangan Daerah Istimewa Yogyakarta, profil responden didominasi oleh: jenis kelamin perempuan (55.9%), tingkat usia ≥ 35 tahun s.d < 50 tahun (49.5%), pendidikan S1 (56.8%), sudah menikah (79.3%), dan masa kerja 11 s.d. 20 tahun (32.4%). Selanjutnya berdasarkan analisis regresi linier sederhana uji t menunjukkan bahwa Work Experience, Work Environment, dan Job Satisfaction secara parsial berpengaruh positif dan signifikan terhadap Performance Pegawai di Dinas Pertanian dan Ketahanan Pangan Daerah Istimewa Yogyakarta. Berdasarkan hasil analisis regresi linier berganda uji F, menunjukkan bahwa Work Experience, Work Environment, dan Job Satisfaction secara simultan berpengaruh positif dan signifikan terhadap Performance Pegawai di Dinas Pertanian dan Ketahanan Pangan Daerah Istimewa Yogyakarta. Kata kunci: Work Experience, Work Environment, Job Satisfaction, Performance.